Pembelajaran Pendidikan Agama Islam dengan Menggunakan Aplikasi Quiziz pada Era Covid-19 - Armi Gusvita (Intiqad: Jurnal Agama dan Pendidikan Islam, 2021)
This article explains about the increased student activity during the covid-19 pandemic by using quiziz application in Islamic Religious Education learning. Quiziz has the advantage of being able to provide a pleasant atmosphere for students with music and pictures that change. Students will race in getting the highest rank because this quiziz uses a rating system. Playing games with this quiziz app can provide an experience for students. This research uses descriptive qualitative methods, data collection techniques used for observation, interviews and documentation. The results of this study showed the use of quiziz in PAI learning makes the activities and learning outcomes of students so increased, from 31 students who were previously only active 15 people, but after using the quiziz application has increased and can also improve the learning results that were previously only completed 7 people, but after using the quiziz application to 20 students.